Over-confidence and low-cost heuristics: An experimental investigation of choice behavior - Simona Cicognani; Luigi Mittone (Economics: The Open-Access, Open-Assessment E-Journal, 2014)
This paper extends choice theory by allowing for the interaction between cognitive costs and imitative dynamics. The authors experimentally investigate the role of imitation when participants face a task which is costly in cognitive terms. In order to disentangle different choice dynamics, they devise a laboratory experiment with a novel experimental task in which they model the choice of different alternatives through high or low cognitive costs and feedback information provided to subjects. Their results provide evidence for imitative behavior driven by under-confidence about own skills and by the beliefs regarding others' performance. They also find a temporal pattern in the distribution of choices, both in the high-cost and low-cost cognitive conditions, that may represent another cognitive shortcut.
Keywords: C91; D80; D81; D83; 330; Belief; cognitive costs; decision making; laboratory experiments